Environmental management systems (EMS) - Zahari, Muhammad Syaiful Annuruddin; Hasbullah, Mohd Hanif; Zulkafli, Nurul Farhana; Hassan, Hassan Hussein; Aden, Mohamed Ibrahim (Penerbit UTHM, 2020)
The chapter aimed to review the environmental management system (EMS) on the company’s workplace. The implementation of EMS ISO 14001 was reviewed at two companies; Fujitsu Component Sdn. Bhd. and Evergreen Fibreboard Bhd. The company with EMS ISO 14001 policy has effects to implement proper waste management system. More cooperation and knowledge implementation required in maintain ongoing environmental payback, cost savings and contribute to building attractive work place traditions.